Leading with values: scenario-based case studies - Azman, Amelia Wong; Abdul Ghani, Zurina; Wan Zulkifle, Wan Zahidah; Musa, Muhammad Adli; Din@Yaakob, Rusnani (IIUM Leadership Centre, 2025)
In today’s complex and evolving higher education landscape, leadership requires more than just technical skills—it calls for values-driven action, adaptability, and a deep understanding of personal and organisational dynamics. Leading with Values: Scenario-Based Case Studies, inspired by the human-centred approach outlined in Humanising Leadership: Transforming the Education Landscape, serves as a vital guide for selecting future leaders in Malaysian higher education institutions. It highlights the essential qualities and competencies needed to excel in leadership roles and underscores the pivotal role of ethical and inclusive leadership in addressing real-world challenges.